NMR reveals the metabolic changes induced by auranofin in A2780 cancer cells: evidence for glutathione dysregulation. Issue 18 (22nd April 2021) - Ghini, Veronica; Senzacqua, Tommaso; Massai, Lara; Gamberi, Tania; Messori, Luigi; Turano, Paola
Abstract : NMR-based metabolomics is used to characterize the metabolic phenotype of auranofin treatment in A2780 ovarian cancer cells. The most distinctive trait is an early and evident increase of intracellular GSH, a key molecule in cell redox metabolism. Abstract : NMR metabolomics represents a powerful tool to characterize the cellular effects of drugs and gain detailed insight into their mode of action. Here, we have exploited NMR metabolomics to illustrate the changes in the metabolic profile of A2780 ovarian cancer cells elicited by auranofin (AF), a clinically approved gold drug now repurposed as an anticancer agent. An early and large increase in intracellular glutathione is highlighted as the main effect of the treatment accompanied by small but significant changes in the levels of a few additional metabolites; the general implications of these findings are discussed in the frame of the current mechanistic knowledge of AF.